HUBUNGAN KREATIVITAS, EFIKASI DIRI DAN INTENSI BERWIRAUSAHA PADA MAHASISWA - Rr. Ponco Dewi Karyaningsih; Agus Wibowo (Jurnal Pendidikan Ekonomi dan Bisnis (JPEB), 2017)
This study aims to determine: (1) The relationship between creativity with the intention of entrepreneurship Faculty of Economics (FE), State University of Jakarta (UNJ); (2) The relationship between self-efficacy with student entrepreneurship intention of FE UNJ, and (3) The relationship between creativity and self efficacy with student entrepreneurship intention of FE UNJ. This research uses survey method with correlation approach. Correlation approach used to see the influence between three independent variables creativity and self efficacy that influence and given symbol X1 and X2, with dependent variable of entrepreneurship intention as influenced and given symbol Y. The result of research indicate that: (1) there is significant correlation between creativity with student entrepreneurship intention of of FE UNJ, where coefficient of double correlation coefficient (Ry.12) = 0,545 and F count (F Change) = 62,672 and p-value = 0,000 <0,05, and coefficient of determination or R square = 0 , 29; (2) there is a significant correlation between self efficacy with student entrepreneurship intention of of FE UNJ, where the coefficient of double correlation (Ry.12) = 0,581 and F count (F Change) = 75,571, and p-value = 0,000 <0,05 , and the coefficient of determination R square = 0,388; (3) there is a significant correlation between creativity and self efficacy to student entrepreneurship intention of of FE UNJ where the result of double correlation test (Ry.12) = 0,635 and F count (F Change) = 49,785, and p-value = 0,000 < 0.0, and the coefficient of determination (R square) = 0.404.